Development of a Poetry Writing Enrichment Book Containing Javanese Art Using the Kvisoft Flipbook Maker Application - Wicaksono, Harits Agung; Setyaningsih, Nas Haryati Setyaningsih; Wagiran, Wagiran (Universitas Negeri Semarang, 2023)
Enrichment books can support textbooks used in learning, where these books can provide an in-depth study of the material being taught. The aims of this research are (1) to analyze the need for enrichment books for writing poetry containing Javanese art using the Kvisoft Flipbook Maker application; (2) development of a prototype for an enrichment book for writing poetry containing Javanese art using the Kvisoft Flipbook Maker application; (3) analyzing the acceptability of poetry writing enrichment books containing Javanese art using the Kvisoft Flipbook Maker application. This research design uses Research and Development (R&D) research. The data sources for this research come from students, educators and validators. Data analysis techniques in development research combine qualitative and quantitative data. The results of this research consist of three things, including: (1) analysis of the needs for enrichment books for students and educators regarding enrichment books for writing poetry containing Javanese art using the Kvisoft Flipbook Maker application from the aspects of book content, book presentation, book language and readability, and book graphics ; (2) development of a prototype for an enrichment book for writing poetry containing Javanese art using the Kvisoft Flipbook Maker application which includes aspects of the book cover, beginning of the book, contents of the book, and end of the book, which was then validated by experts. Experts' assessments and suggestions were taken into consideration by researchers in revising the book prototype; (3) the acceptability of a poetry writing enrichment book containing Javanese art using the Kvisoft Flipbook Maker application was analyzed through four aspects, including: book content, book presentation, book language and readability, and book graphics. The results of this analysis prove the suitability of the book to user needs and the accuracy of the Javanese art content contained in the book.